La revalorisation d’une unité paysagère «le bardo de Constantine » Projet : musée de bardo, musée botanique - BOUCHAMA, Hanine; Mr. BOUKELOUHA, Radhwane (Encadreur) (Université Ferhat Abbas Sétif 1. Institut d'architecture et sciences de la terre. Département d'architecture, 2016)
A link between the past and the present, the landscape become a heritage fact. The necessity for the future generations calls us to preserve this heritage. This study was applied on one of historical sitesin Constantine city. “The Bardo district” for its rich heritage and its high value landscape which has a quite contrast image. Needs to be developed and high valued. The primary objective of this work is to try to improve the landscape image of the district and high value itthrough an intervention on the north side of the field to allow opening the district on the rest of the city. One of the proposal axes i s the creation of a public equipment destined for a botanic conservation that had educational, didactic and scientific purposes. At the same, time a place for a rest. Friendliness and meetings. This work is a test of revalued the area/district with always give importance to the existing fabric. Which explain its rationality and its objectivity.
.رابط بين الماضي والحاضر، لقد أصبح المنظر يمثل التراث من اجل سهولة انتقاله للأجيال القادمة معرفته أوجبت علينا ضرورة الحفاظ عليه. هذه الدراسة تجسدت على واحد من المواقع الأثرية لمدينة قسنطينة والذي يدعى حي باردو" ونظرا لثرائه التاريخي وطبيعته الخلابة ومناظره المتباينة.الهدف الرئيسي من هذه الدراسة هو محاولة تحسين وتطوير مشهد الحي من خلال التدخل من الجهة الشمالية للحي والسماح بفتحها .لباقي المدينة واحدة من الطرق المقترحة هي إنشاء مرفق عام للمحافظة على النباتات، لأغراض تعليمية وتربوية وعلمية، وكمساحة للاسترخاء، الالتقاء والاجتماع بين الأصدقاء هذا العمل هو تجربة لترقية الحي مع الاخذ بعين الاعتبار البنية التحتية القائمة وهذا ما يفسر العقلانية والموضوعية للحي.
Keywords: Paysage; Patrimoine; Constantine; Bardo; Revalorisation